NORMALIZATION OF DIFFICULT LOAN PAYMENTS: A SEMIOTIC ANALYSIS OF LOAN SERVICE ADVERTISEMENT IN POST PANDEMIC ERA - Fani Indrawan; Nimas Diah Putri Ayu Dewi Nastiti (Program Studi Pendidikan Bahasa Inggris,, Fakultas Ilmu Pendidikan, Universitas Hasyim Asy'ari, 2022)
This study focuses on semiotic analysis of Kredivo's commercial video entitled